2019
DOI: 10.1111/jan.14285
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being and thriving in sheltered housing versus ageing in place: Results from the U‐age sheltered housing study

Abstract: Aims To explore to what extent type of residence (sheltered housing or ageing in place) contributes to thriving and well‐being in older adults, when controlling for age, sex, living alone, being a widow and adjusting for functional status, self‐rated health, and depressive mood. Design A matched cohort study. Methods A self‐report survey was sent out to a total population of residents in all sheltered housings in Sweden and a matched control group ageing in place (N = 3,805). The data collection took place bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Studies from the UK, Ireland and the Netherlands, which were based on smaller samples, showed little difference in mobility and health between those living in sheltered housing and aging in place (Fox et al 2017;Van Bilsen et al 2008); however, one study found higher rates of activity limitation and depression among residents living in sheltered housing (Field et al, 2002). As previous studies on the same sample residing in Swedish sheltered housing has shown statistically significant differences between groups in relation to in functional status, depressive mood, thriving in relation to the fore mentioned, and living alone (Corneliusson et al, 2019a), it can be hypothesized that these may be predictors for relocation to nursing home.…”
Section: Relocation Patterns and Predictors Of Relocation And Mortali...mentioning
confidence: 85%
See 1 more Smart Citation
“…Studies from the UK, Ireland and the Netherlands, which were based on smaller samples, showed little difference in mobility and health between those living in sheltered housing and aging in place (Fox et al 2017;Van Bilsen et al 2008); however, one study found higher rates of activity limitation and depression among residents living in sheltered housing (Field et al, 2002). As previous studies on the same sample residing in Swedish sheltered housing has shown statistically significant differences between groups in relation to in functional status, depressive mood, thriving in relation to the fore mentioned, and living alone (Corneliusson et al, 2019a), it can be hypothesized that these may be predictors for relocation to nursing home.…”
Section: Relocation Patterns and Predictors Of Relocation And Mortali...mentioning
confidence: 85%
“…Previous quantitative studies on Sweden sheltered housing have shown that residents in sheltered housing report higher depressive mood, and lower levels of health, health-related quality of life, and functional status, when compared to those aging in place, implying potential health-care needs existing or arising among residents in sheltered housing (Corneliusson et al, 2019b). Study on the same sample also revealed that while experiencing increasing level of depressive mood, and decreasing levels of health and functional status, residents in sheltered housing generally reported higher levels of thriving, when compared to those aging in place, implying that there are features within sheltered housing that support thriving (Corneliusson et al, 2019a). Thriving, which has recently been defined as a concept that denotes lived experiences of situated contentment, provides novel insight into the interplay of different features that may affect wellbeing in a specific context (Baxter et al, 2021).…”
Section: Relocation Patterns and Predictors Of Relocation And Mortali...mentioning
confidence: 87%
“…Drawing on the life-course and environmental perspectives, researchers have recognized that the living environment, that is, the physical and social context among low-income adults, significantly influences their ability to age well ( Wahl et al, 2012 ). Recent work suggests that older adults living in congregate housing (independent living, assisted living, co-housing) report higher levels of “thriving” than those “aging in place” in the community, despite experiencing lessened functional independence and self-rated health ( Corneliusson et al, 2020 ). Some features of congregated senior housing contribute to positive effects on the well-being of these residents as they may experience increased social interaction, participation, activities, safer environment, and access to supportive services than adults aging at home ( Litwin & Stoeckel, 2014 ; Taube et al, 2014 ).…”
Section: Intervention Programs Health and Quality Of Life For Adults ...mentioning
confidence: 99%
“…Also, they more frequently reported problems with anxiety and depression, and had lower self-reported quality of life, but their self-reported wellbeing was higher. In a paper reporting on another aspect of the same study,Corneliusson et al (2020) functional, cognitive and mental health. The study also found AL SIH residents had significantly lower serum 25-OH vitamin D levels indicating poor diet, long periods of time spent indoors, and higher risk of developing vitamin deficiency-related health problems.…”
mentioning
confidence: 99%
“…Also, they more frequently reported problems with anxiety and depression and had the lower self-reported quality of life, but their self-reported well-being was higher. In a paper reporting on another aspect of the same study,Corneliusson et al (2020) attempted to explain this paradox. They proposed that accessibility to increased safety and better home design/adaptations, and opportunities for meaningful activity in SA SIH contributed to residents' well-being Avery et al (2010).…”
mentioning
confidence: 99%